2017
DOI: 10.1016/j.envres.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Combustion-derived nanoparticles, the neuroenteric system, cervical vagus, hyperphosphorylated alpha synuclein and tau in young Mexico City residents

Abstract: Mexico City (MC) young residents are exposed to high levels of fine particulate matter (PM), have high frontal concentrations of combustion-derived nanoparticles (CDNPs), accumulation of hyperphosphorylated aggregated α-synuclein (α-Syn) and early Parkinson's disease (PD). Swallowed CDNPs have easy access to epithelium and submucosa, damaging gastrointestinal (GI) barrier integrity and accessing the enteric nervous system (ENS). This study is focused on the ENS, vagus nerves and GI barrier in young MC v clean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 119 publications
0
28
0
3
Order By: Relevance
“…Furthermore, it has been reported that residents from the north area have been exposed to higher PM 10 and PM 2.5 concentrations with high levels of the following metals: Mn, Zn, Cu, Pb, Ti, Sn, V and Ba. 10 On the other hand, if Mn distribution was dominated by natural sources, it would be expected that the highest concentrations were located around the city, near the less urbanized sites or towards the southeast because of the active Popocatépetl volcano, as the volcanic activity is one of Mn main natural sources. 4 By estimating the spatial distribution of Mn load contamination, a strong influence of street dust load was observed, as the areas with the highest Mn load were located towards the east and northwest of the city, where there was more dust.…”
Section: Spatial Distribution Municipal Analysis and Human Health Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that residents from the north area have been exposed to higher PM 10 and PM 2.5 concentrations with high levels of the following metals: Mn, Zn, Cu, Pb, Ti, Sn, V and Ba. 10 On the other hand, if Mn distribution was dominated by natural sources, it would be expected that the highest concentrations were located around the city, near the less urbanized sites or towards the southeast because of the active Popocatépetl volcano, as the volcanic activity is one of Mn main natural sources. 4 By estimating the spatial distribution of Mn load contamination, a strong influence of street dust load was observed, as the areas with the highest Mn load were located towards the east and northwest of the city, where there was more dust.…”
Section: Spatial Distribution Municipal Analysis and Human Health Rmentioning
confidence: 99%
“…9 Recently, medical concern has been raised in Mexico City because children and youth are already exhibiting early Parkinson disease neuropathological hallmarks. 10 Mn could be a cause; however, there is no information on Mn concentration amounts in Mexico City's environment.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha reportado que la presencia y la cantidad de los diferentes metales encontrados en las partículas varían de acuerdo con la zona geográfica (24) , y con la época del año; las PM 10 transportan mayor cantidad de Ti que las PM 2,5 (26) . En líneas celulares (27) , así como en la población expuesta, en especial los niños, se han observado procesos inflamatorios en grados que varían según el lugar de residencia y el tiempo de exposición (7) , desconociéndose si el Ti, elemento no esencial para la vida humana, se acumula en el tejido respiratorio de la población expuesta a la contaminación del aire en la ciudad de México. El objetivo del presente estudio fue identificar la presencia de TiO 2 en muestras de tejido respiratorio de personas que residieron en la Ciudad de México.…”
Section: En Trabajadores Expuestos Ocupacionalmente Al Tio 2 Yunclassified
“…El conocimiento actual sobre la toxicidad del dióxido de titanio (Ti) proviene de estudios experimentales en vivo e in vitro (1)(2)(3)(4)(5) , en los que se informa que el óxido de titanio (TiO 2 ) puede ser absorbido principalmente a través del tracto digestivo, respiratorio y, dependiendo del tamaño de las partículas, llegar al torrente circulatorio y ser distribuido y acumulado en hígado, bazo, riñón, pulmón, ganglios (6) y cerebro (2,7,8) .…”
Section: Mensajes Clave Introducciónunclassified
“…In children and young adults, NPs are found to be associated with major abnormalities in subcellular organelles. [19][20][21] Therefore, studies should be oriented toward investigating the interaction of TiO 2 NPs with some biological systems such as the nervous system. Here, we tried to explore the interaction of TiO 2 NPs with tau and the cytotoxicity of TiO 2 NPs/ tau complex against SH-SY5Y as models of nervous systems in vitro by biophysical, bioinformatic, and cellular assays.…”
Section: Introductionmentioning
confidence: 99%